Differences in author ranking: Development of SIGAPS scoring system for Japanese version. (9th July 2020) - Nishizaki, Yuji; Homma, Yasuhiro; Ueda, Rieko; Devos, Patrick; Sanada, Shoji
Abstract : Although the SIGAPS scoring system is extremely beneficial in evaluating the quality of academic papers and individual research achievement, values for author ranking may vary by country. If a SIGAPS scoring system outside of France is considered, the weighting by author ranking should also be reconsidered.